Profissionalização docente na educação infantil no município de São Carlos - SP: a sobreposição da lógica educacional à lógica assistencialista - Bueno, Jaqueline Cristina dos Santos (2022)
The present study addresses organizational change with a focus on the transition from welfare to educational logic in early childhood schools in the city of São Carlos, using a survey on the training and specialization of the teaching staff to analyze this process. Data obtained from the Municipality of São Carlos and interviews with teachers from the municipal early childhood education network were used for this purpose. Faced with social changes related to the way of seeing the child as a social actor, theories began to value the experiences and experiences of this age group, and this had an impact on education. Initially, daycare centers were designed with a more assistentialist character, supervised by the Social Assistance Department, with a focus solely on the care and hygiene of children. Professionals who worked directly with students did not need any training, since early childhood education was not part of basic education . Since the 1990s, several laws have brought about changes in child care. This required an adjustment on the part of professionals and managers of the teaching organization. A process of encouraging the continuing education of professionals working in education was initiated. Thus modifying the routine, the assessment methods, and consequently the skills developed. It was noted that the vast majority of professionals had their level of education increased during their professional lives and continuing education is something present in the school calendar. It can be concluded, therefore, that even when caring is associated with educating in early childhood education, the assistentialist logic of the day care center has been gradually replaced by the educational logic, and it is possible to verify an overlap between the two logics at times through the perspectives and modes thinking, as well as everyday attitudes already established in the organization's routine.